Implementing dual system vocational education in industrial polytechnic: A case study of Banten Petrochemical Polytechnic - Astuti, Ismaya Indri (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2026)
Human resources development plays a crucial role in supporting the implementation of the Making Indonesia 4.0 roadmap. Vocational education is expected to produce graduates who possess competencies aligned with industrial needs. This study aims to analyze the implementation of the Dual System vocational education curriculum at Banten Petrochemical Industry Polytechnic, one of the industrial polytechnics under the Ministry of Industry of Indonesia. This research employed a qualitative approach using observations, interviews, documentation, and document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that the implementation of the Dual System curriculum is supported by several key strategies, including strong industry partnerships, curriculum alignment with industrial needs, block-based learning systems combining theory and practice, the involvement of industry practitioners in teaching, and continuous capacity development for lecturers. These strategies contribute to strengthening students’ practical competencies and improving their readiness for industrial work environments. The study highlights the importance of institutional collaboration between vocational education institutions and industries in developing industry-relevant human resources in the era of Industry 4.0.